Interfaith Waqf in Central Kalimantan: Transformation of Islamic Financial Institutions from the Perspective of Legal Pluralism - Aswad, Muhammad; Wakhidah, Nur; Qomar, Mujamil; Majid, Abdul; Muh. Arief Budiman (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2026)
Waqf has long been conceptualized as a form of religious endowment governed by established doctrinal and institutional frameworks. However, contemporary practices in plural societies increasingly challenge this conventional understanding. In particular, interfaith expressions of waqf invite a reconsideration of the boundaries of Islamic social finance and its capacity to adapt within diverse social settings. This study seeks to analyze how interfaith waqf practices reshape the normative, social, and institutional dimensions of waqf, while also examining their implications for social cohesion and processes of institutional transformation. This research adopts a qualitative field-based approach, utilizing in-depth interviews, direct observation, and documentary analysis conducted in Tewah District, Central Kalimantan. The findings indicate that waqf may originate from non-Muslim actors and operate as a socially embedded practice sustained through interfaith collaboration, shared ethical commitments, and forms of legitimacy rooted in community recognition. At the same time, the lack of formal legal acknowledgment points to a persistent gap between regulatory structures and lived social practices. The study concludes that interfaith waqf can be understood as an adaptive and practice oriented form of Islamic social finance, in which institutional change is shaped primarily by everyday social interactions rather than formal legal arrangements. These findings emphasize the importance of developing a legal pluralism approach that is more responsive to local contexts, and contributes to efforts to reconceptualize waqf as an inclusive institution rooted in social realities in plural societies.